Laying the Groundwork for Artificial Intelligence Policy: A Preliminary Assessment of Indonesian Governance Using UNESCO's RAM Framework - Sajida Sajida; Ryza Dani Pratiwi (Universitas 17 Agustus 1945 Semarang, 2025)
The present study reflects upon the initial evaluation of Indonesia's readiness for the ethical adoption of artificial intelligence (AI) per the available evaluation framework, namely, the UNESCO Readiness Assessment Methodology (RAM). The analysis considers key legal, social, scientific, economic, and technical dimensions pertaining to governance of artificial intelligence in Indonesia, with the view to exploring particular gaps and opportunities for improvement. Following a detailed secondary-document analysis, this study underscores the capacity of the country to apply AI within economic, governance, and sustainable development domains while tackling ethical challenges. The study also makes recommendations for legal systems and frameworks, infrastructure, and interdisciplinary collaboration. The limitations of the present assessment are indicated, alongside guidance for future studies to pursue an inclusive and sustainable AI ecosystem in Indonesia.